Contagion and learning in business networks - Peters, Linda D.; Pressey, Andrew D.; Johnston, Wesley J. (Elsevier, 2017)
The purpose of this study is to examine network learning through the application of contagion theories. The transmission of knowledge, sharing of resources, and facilitation of learning through contagion has interested both business-to-business and economic geography researchers. This study responds to calls in both research traditions for research into knowledge and learning at the level of an interfirm network. More specifically, it focuses on developing an understanding of how the contagion of knowledge and ideas and the co-ordination of activities within a network tales place. We achieve this by drawing upon research in both network relationships dynamics and learning processes to investigate the causal mechanisms that drive contagion. We focus on two types of contagion: contagion by cohesion (i.e. the presences and closeness of direct contact with others in the network), and contagion by structural equivalence (i.e. where influence is related to the structural patterns of relationships in the network). We also identify two key mechanisms that act as a barrier to such contagion: isolation and immunity. We explore the implications of these findings for network learning opportunities, specifically learning-by-doing, learning-by-using, and learning-by-interacting.